Exogenous silicon enhances the systemic defense of cucumber leaves and roots against CA-induced autotoxicity stress by regulating the ascorbate-glutathione cycle and photosystem II - Xin Meng (Elsevier, 2021)
Cinnamic acid (CA), one of the main autotoxins secreted by cucumber roots during continuous cropping, inhibits plant growth and reduces yield. Silicon (Si) is an environmentally friendly element that alleviates abiotic stresses in plants, but the mechanism underlying its resistance to autotoxicity remain unclear. Here, we used 0.8 mmol L−1 CA to study the effects of Si application on the growth, chlorophyll fluorescence, and ascorbate-glutathione (AsA-GSH) cycle of cucumber seedlings under CA inducing conditions. Our results indicated that CA significantly induced photoinhibition and overaccumulation of reactive oxygen species (ROS), thereby inhibiting cucumber growth. Treatment with 1.0 mmol L−1 Si improved plant height, stem diameter and biomass accumulation, and protected the photosynthetic electron transport function of photosystem II in the presence of CA. Similarly, Si application maintained the ROS status by increasing ascorbate (AsA) and glutathione (GSH) production, as well as the ratios of AsA/DHA and GSH/GSSG in both leaves and roots during CA stress. In addition, Si application in CA-treated seedlings enhanced the activity of key enzymes such as ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR), glutathione reductase (GR), glutathione S-transferase (GST), and the transcription of several enzyme genes (CsAPX, CsMDHAR and CsGR） from the AsA-GSH cycle. These results suggest that exogenous Si enhances CA tolerance in cucumber seedlings by protecting photosystem II activity, upregulating AsA-GSH pathway, and reducing ROS levels.